2022
DOI: 10.1177/23259671221086920
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Platelet-Rich Plasma for Lateral Epicondylitis: A Systematic Review and Meta-analysis Based on Achievement of Minimal Clinically Important Difference

Abstract: Background: The effectiveness of platelet-rich plasma (PRP) injection in the treatment of lateral epicondylitis remains debatable. Purpose: To evaluate the effectiveness of PRP in lateral epicondylitis treatment using minimal clinically important difference (MCID) values as a reference and to investigate if leukocyte content can influence the effectiveness of the therapy. Study Design: Systematic review; Level of evidence, 4. Methods: Following the PRISMA (Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Niemiec et al, in their meta-analysis of 26 studies with PRP injection for lateral epicondylopathy, established the treatment as effective in the achievement of MCID during all points of follow-up (4-104 weeks) [16]. In another meta-analysis based on 16 studies, Chen et al, found that despite a significant clinical improvement, they were unable to recommend for or against the use of PRP for lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Niemiec et al, in their meta-analysis of 26 studies with PRP injection for lateral epicondylopathy, established the treatment as effective in the achievement of MCID during all points of follow-up (4-104 weeks) [16]. In another meta-analysis based on 16 studies, Chen et al, found that despite a significant clinical improvement, they were unable to recommend for or against the use of PRP for lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was considered effective if a minimal clinically important difference (MCID) occurred in pain reduction, or a functional improvement between the baseline and follow-up periods. According to the literature, a MCID is equal to 1.5 points for the VAS, 15.8 points for the DASH, and 11 points for the PRTEE [16].…”
Section: Evaluation Of Treatment Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite many years of research, the gold standard of treatment has not been established. More and more reports prove the usefulness of autologous platelet-rich plasma (PRP) in the treatment of TE [ 2 , 3 , 4 , 5 ]. This therapy is used in many fields of medicine, including regenerative and sports medicine [ 6 ].…”
Section: Introductionmentioning
confidence: 99%